Persistent T‐cell exhaustion in relation to prolonged pulmonary pathology and death after severe COVID‐19: Results from two Norwegian cohort studies. (18th August 2022) - Trøseid, Marius; Dahl, Tuva B.; Holter, Jan C.; Kildal, Anders B.; Murphy, Sarah L.; Yang, Kuan; Quiles‐Jiménez, Ana; Heggelund, Lars; Müller, Karl Erik; Tveita, Anders; Michelsen, Annika E.; Bøe, Simen; et al.
Abstract: Background: T‐cell activation is associated with an adverse outcome in COVID‐19, but whether T‐cell activation and exhaustion relate to persistent respiratory dysfunction and death is unknown. Objectives: To investigate whether T‐cell activation and exhaustion persist and are associated with prolonged respiratory dysfunction and death after hospitalization for COVID‐19. Methods: Plasma and serum from two Norwegian cohorts of hospitalized patients with COVID‐19 ( n = 414) were analyzed for soluble (s) markers of T‐cell activation (sCD25) and exhaustion (sTim‐3) during hospitalization and follow‐up. Results: Both markers were strongly associated with acute respiratory failure, but only sTim‐3 was independently associated with 60‐day mortality. Levels of sTim‐3 remained elevated 3 and 12 months after hospitalization and were associated with pulmonary radiological pathology after 3 months. Conclusion: Our findings suggest prolonged T‐cell exhaustion is an important immunological sequela, potentially related to long‐term outcomes after severe COVID‐19. Abstract :